Ko-Eksistensi Hukum Negara dan Hukum Adat Bali Dalam Pengangkatan Anak (Studi di Desa Adat Lantangidung, Kecamatan Sukawati, Kabupaten Gianyar) - Ketut Rai Mahajony; I Made Suwitra; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2021)
Traditional Balinese marriages follow the male bloodline (patrilineal), so having a son is still the goal of a marriage. Adoption of children (sentana peperasan) is an option if the family has no children to continue the obligations towards the family and society. Several cases of adoption, such as in the case of adoption in Lantangidung Village, Gianyar Bali, were raised in this study as case studies. The problem raised is how legal the adoption of children is according to Balinese Customary Law and State Law and the position of adopted children in the family and society according to Balinese Customary Law. This research is expected to expand the legal knowledge of the community, especially regarding the combination of Balinese Customary Law and State Law in terms of adoption. An empirical approach is used to see the combination of Balinese Customary Law and State Law. The conclusion is that: the co-existence of Balinese customary law and state law in the implementation of adoption needs to be clarified in more detail with an easy-to-understand sequence of implementation so that the position of adopted children in the family and society is also strong.